2011
DOI: 10.1590/s1679-45082011rc2025
|View full text |Cite
|
Sign up to set email alerts
|

Peritonitis due to Rhizobium radiobacter

Abstract: Rhizobium radiobacter (Agrobacterium radiobacter) is an aerobic Gram-negative rod belonging to Agrobacterium genus, a group of phytopathogenic bacteria present in the soil that has been implicated in human opportunistic infections. We report a clinical case of bacterial peritonitis in a 5-year-old child with chronic renal disease in peritoneal dialysis, who had a history of direct soil contact identified. The infection was treated with ceftazidime and piperaciline+tazobactam without relapses or the need to rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Possibly soil contamination and unsterile techniques could explain relapsed infection in these cases, and thus catheter required removal. Of the 15 reported instances of R. radiobacter -induced peritonitis, six successfully kept the peritoneal catheter intact and resumed PD [ 8 , 13 , 16 , 17 , 20 , 21 ]. Our case adds to this complicated organism’s successful treatment of peritonitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Possibly soil contamination and unsterile techniques could explain relapsed infection in these cases, and thus catheter required removal. Of the 15 reported instances of R. radiobacter -induced peritonitis, six successfully kept the peritoneal catheter intact and resumed PD [ 8 , 13 , 16 , 17 , 20 , 21 ]. Our case adds to this complicated organism’s successful treatment of peritonitis.…”
Section: Discussionmentioning
confidence: 99%
“…Other antibiotics that have been effective include piperacillin-tazobactam, meropenem, and ciprofloxacin. However, it can be argued that in cases where catheter removal was not required, ceftazidime was the most used antibiotic and thus can be recommended as a treatment choice [ 13 , 16 , 17 , 21 ]. Three weeks of duration were pursued in a few cases because of the risk of catheter removal.…”
Section: Discussionmentioning
confidence: 99%
“…organisms that cause the death and disease of many fish are widely distributed in water (Al-Shemmari, 2017). Rhizobium radiobacter is originally characterised as an endo fungal bacterium, an uncommon opportunistic pathogen present in soil as an aerobic gram-negative belonging the Agrobacterium genus (Guo et al, 2017;Marta et al, 2011). Furthermore, A. hydrophila has been recorded in three marine fish species from the North West Arabian Gulf, Iraq (Al-Maleky and Hanafi ,2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…2,7 The catheter preservation rate has increased from 33% (4 of 12 cases) in the 1990s to 2000s 1,6-13 to 67% (four of six cases) in the 2010s. [2][3][4][5]14 One reason for this improvement may be the use of fluoroquinolone antibiotics. In a previous report, Alnor et al suggested that ciprofloxacin might be the drug of choice.…”
mentioning
confidence: 99%
“…Besides fluoroquinolones, this pathogen is usually sensistive to aminoglycosides, third-generation cephalosporins, cephamycins, and carbapenems. 2,7 Among the reported cases of R. radiobacter peritonitis, a combination of two antibiotics, which the bacterium was possibly sensitive to, was administered in six cases, [10][11][12][13][14] and catheter was preserved in five of the six cases [11][12][13][14] (Table 1). In case of peritonitis due to refractory bacteria, a combination therapy of two sensitive antibiotics may be effective.…”
mentioning
confidence: 99%